Ethical challenges in study design and informed consent for health research in resource-poor settings - Marshall, Patricia Loomis (World Health Organization, 2007)
This review considers ethical challenges to research design and informed consent in biomedical and behavioral studies conducted in resource-poor settings. A review of the literature explores relevant social, cultural, and ethical issues in the conduct of biomedical and social health research in developing countries. Ten case vignettes illustrate ethical challenges that arise in international research with culturally diverse populations. Recommendations for researchers and policy-makers concerned about ethical practices in multinational studies conducted in resource-poor settings are also listed.
Special topics, ISSN 1683-5409 no. 5
Keywords: etika, bioetika, lékařská etika; Principle-Based Ethics; etika založená na principech; Research; Informed Consent; Developing Countries; rozvojové země; informovaný souhlas pacienta; výzkum